Preferred Oral Corrective Feedback through Existing Internalized Language Prejudice of Students in the Philippines: A research study done in selected schools in Luzon - Yaneza, Monica Louise; Miralles, Claire Rose; Morales, Jv Andrew; Cao, Geneva; Cruz, John Louie; Orga, Ma. Ericca; Reodava, Kurt Christian (International Journal of Language and Literary Studies, 2024)
Following the 2022 Program for International Student Assessment (PISA) test results, it was found out that the Philippines ranked 76th in reading comprehension among 81 PISA-participating countries. Students from the Philippines are still among the least proficient in the world in reading comprehension. With the country performing below the standards and criterion set by the organization, the researchers investigate internalized language prejudice as learners’ primary obstruction in acquiring the English language. Provided that the Oral Corrective Feedback (OCF) is essential for students’ learning process and performing separate functions in acquiring the English language, this paper aims to figure out their preferred OCF in acquiring the language. Furthermore, the proponents of the study delve into the reasons of the selected students when given an OCF in connection and relevance with how internalized language prejudice, stereotypes, and preconceived notions come into play in terms of the effectiveness of the English language learning and teaching. Lastly, the paper used mixed methods in gathering data: quantitative through an online survey form and qualitative through Focus Group Discussions (FGD).